Pengaruh Bahan Ajar Fisika Berbasis Kontruktivis dengan Pembelajaran Inkuiri pada Materi Pokok Dinamika Rotasi dan Hukum Hooke untuk Meningkatkan Literasi Sains Siswa Kelas XI SMAN 1 V Koto Kampung Dalam - Lisa Herlina Herlina; Hufri - - (Universitas Negeri Padang, 2019)
This study aims to determine the effect of the use of constructivist-based physics teaching materials with inquiry learning on the material of rotational dynamics and hooke laws on the scientific literacy of students at SMAN 1 V Koto Kampung Dalam. Research carried out including the type of quasi experiment research (quasi-experimental). The population of this study is all students of class XI SMAN 1 V Koto Kampung In the 2018/2019 school year. The sampling technique used was purposive sampling technique with the research data taken was student learning outcomes in science literacy skills. The research instrument is the final test to measure the ability of scientific literacy. The research data were analyzed using two similarity test averages. Based on data analysis, the average value of students' scientific literacy for the two sample classes (experimental and control) prior to the study was 17.73 and 23.67, and after the study the average values were 64.09 and 60.83 . T test analysis shows the value of p>α so that the alternative hypothesis is rejected. Due to students 'initial abilities are different, while the final test shows the same average so that the use of teaching materials can be said to affect the increase in students' scientific literacy.